CHARACTER GESTURE COMPARISON ON TIMUN MAS ANIMATION MADE BY DRS SUYADI AND TIMUN MAS ANIMATION MADE BY BENING STUDIO - Amboro, Yudi; Adityayoga, Adityayoga (UI Scholars Hub, 2020)
Animation is one of the flagship products of creative industry which grow rapidly, under Bekraf (Indonesian Creative Economy Board) film, animation, and video sub sector. The high quantity of animation production in Indonesia can be shown through several animation projects which currently still in production stage or already circulated, whether in the form of serialization for TV or in the form of movie on silver screen. Therefore, the study of animation made in Indonesia nowadays is needed more than before. As an art form, animation is also a media that can be deconstructed for each of its aspect, historically, socially, theoretically, and critically. Animation in its visual form is using various element and technique that common in visual media design. This technique historically can be look down to past media that already used before the advent of animation. One of the important visual elements of animation film is visual character element. Visual character is an embodiment of characterization from the scenario. The embodiment done through the design of visual character that made to facilitate the movement in order to make audience understand the story. Character design and its movement in animation through the detail planning must be able to show its personality. In order to show it, the designer uses various technique and methods such as: acting and expression which achieved through character visualization of gesture, movement, voice and other form of body language. Many form of that character visual expression not only used for delivering the story but also to convey meaning to audience. One of the popular genres of animation made in Indonesia is a fairytale (dongeng) animation. Fairytale animation derives its story from folklore (cerita rakyat) of Indonesia. Though it is a misconception the folklore is considered as children friendly story therefore deemed appropriate to be used as animation story for children. One of the popular folklore or fairytale stories that often adapted for animation is Timun Mas story. This animation character gesture study hopefully can be considered as the way to enriching the study of animation as media in Indonesia and in